Human Factors in Information Systems 2002
DOI: 10.4018/978-1-931777-10-0.ch019
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Experience, Culture and Spatial Visualization Ability on Users' Attitudes and Anxiety Towards Computer Use

Abstract: The attitude towards computer-related tasks, computer anxiety, and spatial visualization ability (SVA) of a group of first-year computer science students were measured just before their study commenced. The results were analyzed empirically based on two independent variables, i.e., culture and computer experience. It was found that African and European users generally have the same attitude towards computer use. Users’ attitudes improved after experience with computer-related tasks. African students experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Several researchers have reported differences in attitudes and perceptions of technology among people in different cultures (Singh, Fassott, Chao & Hoffmann, 2006;Haris & Davison, 2002;Blignaut, McDonald & Tolmie, 2002;Durndell, Haag, & Laithwaite, 2000). Other studies conducted in educational environments (Teo, Su Luan, & Sing, 2008;McCoy, Galletta, & King, 2007;Li & Kirkup, 2007) also suggest the possibility of differences in attitudes and perceptions of technology among students in different cultures.…”
Section: Generational and Cultural Differences In Technology Usementioning
confidence: 99%
“…Several researchers have reported differences in attitudes and perceptions of technology among people in different cultures (Singh, Fassott, Chao & Hoffmann, 2006;Haris & Davison, 2002;Blignaut, McDonald & Tolmie, 2002;Durndell, Haag, & Laithwaite, 2000). Other studies conducted in educational environments (Teo, Su Luan, & Sing, 2008;McCoy, Galletta, & King, 2007;Li & Kirkup, 2007) also suggest the possibility of differences in attitudes and perceptions of technology among students in different cultures.…”
Section: Generational and Cultural Differences In Technology Usementioning
confidence: 99%
“…The study also reports a strong correlation between individuals' computer course test scores, their positive attitude towards computers and their positive self-efficacy perception regarding computers. Studies have also reported a correlation between self-efficacy and anxiety towards using computers [27,28]. According to Jawahar and Elango [29], a high degree of computer anxiety leads to negative attitudes towards computer usage.…”
Section: Introductionmentioning
confidence: 99%
“…Harris, Kemmerling and North (2002) found that participants displayed significant differences between computer anxiety levels and personal computer use by cultural variable. Blignaut, Mc Donald and Tolmie (2002) studied university students" computer-related task attitudes, computer anxieties and visual spatial skills. Their findings revealed the African and European students had similar attitudes toward computer use.…”
Section: Cross-cultural Perspectivementioning
confidence: 99%
“…It is known that one of the factors affecting instructional technology-related anxiety level is instructional technology-related attitude (Mc Ilroy, Bunting, Tierney, & Gordon, 2001, Coffin & Mackintyre 2000. Instructional technology-related negative and positive attitudes play a determinant role in anxiety (Blignaut, Mc Donald & Tolmie, 2002). Jawahar and Elango (2001) found that a high computer anxiety led to negative attitudes toward computers.…”
Section: Introductionmentioning
confidence: 99%